2-(4-Chloro-2-nitrophenyl)-4-methoxy-9-phenylsulfonyl-9H-carbazole-3-carbaldehyde - P. Narayanan; K. Sethusankar; Velu Saravanan; Arasambattu K. Mohanakrishnan (Acta Crystallographica Section E, 2014)
In the sterically hindered title compound, C26H17ClN2O6S, the carbazole ring has a maximum deviation from planarity of 0.067 (4) Å for the C atom connected to the aldehyde group. The carbazole moiety forms a dihedral angle of 72.8 (1)° with the nitro-substituted benzene ring. The O atom of the methoxy group deviates by 0.186 (1) Å from the adjacent carbazole moiety. The phenylsulfonyl group forms intramolecular C—H...O bonds between sulfone O atoms and the carbazole moiety, resulting in two S(6) rings. In the crystal, the nitrated benzene rings are linked via C—H...O interactions forming infinite C(7) chains along [100]. The crystal packing is also characterized by C—H...π interactions, which result in inversion dimers.